DEVELOPMENT OF REGRESSION MODELS WITH TIME SERIES DATA ON FISH SEED AND FISH RPODUCTION OF ARUNCHAL PRADESH - Upadhyay, A. D.; Roy, A. K. (Journal of Indian Fisheries Association, 2014)
The present fish production of the State of Arunanchal Pradesh is 2.65 thousand tones against the demand of 13 thousands tones. This gap in demand and supply of fish is filled by importing fish from other States like Andhra Pradesh, West Bengal, Assam etc. In this paper, an attempt has been made to establish trends in seed and fish production that has been obtained by using time series data of the state. Further the relationship between seed production and fish production using exploratory data analysis method has been fitted. An increasing trend in  yearly fish production is witnessed during the year 2000-01 to 2011-12, except declined in 2009-10. The fitted second order prediction equation of fish production (Y) and years (X) is (Ŷ=0.005x2-0.011x+2.580R2=0.767). The overall trend of seed production in the state was observed to be positive during 2000-01 to 2010-11. However, instability in the quantum of the seed production was also reflected due to low R2 value (0.488) and the fitted linear regression equation (Ŷ=0.36x+24.32R2=0.488). The regression analysis showed that seed production in the state had significantly influenced fish production (Ŷ = 0.029x3 – 2.402x2 + 66.00x – 600.4 with R2 = 0.740, where Ŷ is estimated fish production and x is seed production million fry). The trend suggests further emphasis on production and distribution of quality seed in order to enhance fish production in the state. Key words: Fish production, seed production, regression, trend, exploratory data analysis.